Molecular Detection of Parvovirus in Captive Siberian Tigers and Lions in Northeastern China From 2019 to 2021 - Huang, Shuping; Li, Xiang; Xie, Wei; Guo, Lijun; You, Dan; Xu, Haitao; Liu, Dan; Wang, Yulong; Hou, Zhijun; Zeng, Xiangwei; Yang, Siyuan; Chai, Hongliang; et al. (Frontiers in Microbiology, 2022)
The fact that wild felines are carriers of pernicious infectious viruses should be a major concern due to the potential cross-species transmission between the felines and human or domestic animals. However, studies on the virus in the captive wild felines, especially in tigers, are thin on the ground. In this study, we screened four infectious viruses: feline parvovirus (FPV), feline coronavirus (FCoV), canine distemper virus (CDV), and influenza A virus (IAV) in the blood samples of 285 captive Siberian tigers (Panthera tigris altaica) and the spleen samples from two deceased lions (Panthera leo), which were collected from 2019 to 2021 in three Siberian Tigers Parks from the northeast of China. Nucleic acids isolated from blood collected from tigers and spleens from two deceased lions were positive for FPV by PCR, and the positive rate was 4.6% (13/285) in tigers. Furthermore, the VP2 gene of FPV was amplified by nested PCR, and the sequences of the VP2 gene from these six FPV positive strains shared 98.3%–99.9% homology with the reference. The key amino acid sites of VP2 protein were consistent with that of FPV reference strains. Phylogenetic analysis based on the VP2 gene showed that FPV positive strains in this study grouped within the FPV clade and closely related to the Asian strains clade. The results of this study showed that FPV circulated in the captive Siberian tigers and lions in northeastern China, and provided valuable information for the study of FPV epidemiology in wild felines.